The Effect Of Digital Transformation, Technology Adoption, And Innovation On Business Performance - Muhammad Aria Wahyudi; Alfi Rochmi; Tukina; Arisantoso (Journal Management & Economics Review (JUMPER), 2026)
The purpose of the study is to look into the impact that digitalization, technology adoption, and innovation have on the performance of organizations. With technological changes happening rapidly and stiff competition in the markets, organizations must adapt to changes in technology, adopt innovations, and continue improving. The method used in this study is a quantitative method with an explanatory research design. Data was collected from decision-makers within the organizations via structured questionnaires, which were later analyzed using statistical analysis methods, such as multiple regression analysis. From the above results, it is evident that the variables digital transformation, technology adoption, and innovation have a significant and positive effect on the performance of the business. Of all these variables, it is clear that innovation has the highest level of dominance in influencing business performance. Innovation plays an important role in contributing to organizational success. The digital transformation strategy helps the business in improving its efficiency and creating new business models, while technology adoption facilitates better decision-making and increases efficiency. Moreover, from the results, it can be seen that there is a high level of significance associated with the effect of these variables on business performance. Therefore, it is important for companies to integrate these variables together in order to attain their full benefit and gain a competitive edge over others.